Psychological Interaction between Da'i and Mad'u Against the Da'wah Process - Samsinar S.; Sapta Wardana; Ayu Aspila (Palakka : Media and Islamic Communication, 2022)
This study discusses the concept of the psychological interaction of da'i and mad'u, forms of psychological interaction of da'i and mad'u, the process of da'wah and the effect of psychological interaction of da'i and mad'u on the da'wah process. This research is library research with descriptive-qualitative approach. The method and analysis used is an inductive qualitative analysis. Inductive qualitative data analysis is an analysis based on the data obtained, then developed into answers to the problems in this study, and searched for data repeatedly so that the data collected can be known to be accepted or rejected. The results showed that the concept of psychological interaction between the da'i and mad'u is a process of interaction carried out between the da'i and mad'u with the aim of influencing attitudes and behavior so that changes occur in honey which are carried out both consciously and unaware. There are several forms used by da'i in psychological interaction with mad'u, namely providing motivation in behavior, social interaction, communication and leadership. This interaction takes place in the da'wah process through several stages, namely the stage of receiving da'wah material, processing da'wah material, storing da'wah material and producing da'wah material again. With this psychological interaction, it will have a positive influence both da'i and mad'u on the da'wah process so that da'wah runs effectively and efficiently.